Peran Hospital Bylaws Dalam Melindungi Kegiatan Yang Dilakukan Tenaga Kesehatan Di Rumah Sakit - Dinias Catur Wira Kencana Khamdianingsih (Doktrin:Jurnal Dunia Ilmu Hukum dan Politik, 2023)
These regulations are set forth in the rules of the game established in the Hospital specifically for the benefit of the Hospital concerned. Every hospital, in accordance with the law, has many obligations, one of which is to compile and implement hospital internal regulations or also called hospital by laws (RS Law No.44/2009 Ps.29 paragraph (1) letter r). What is meant by Hospital internal regulations (Hospital bylaws) are Hospital organizational regulations (corporate bylaws) and Hospital medical staff regulations (medical staff bylaws) which are prepared in the context of implementing good corporate governance and clinical governance good (good clinical governance).